Helping Autism-Diagnosed Teenagers Navigate and Develop Socially Using E-Learning Based on Mobile Persuasion - Øhrstrøm, Peter (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The HANDS (Helping Autism-diagnosed teenagers Navigate and Develop Socially) research project involves the creation of an e-learning toolset that can be used to develop individualized tools to support the social development of teenagers with an autism diagnosis. The e-learning toolset is based on ideas from persuasive technology. This paper addresses the system design of the HANDS toolset as seen from the user’s perspective. The results of the evaluation of prototype 1 of the toolset and the needs for further development are discussed. In addition, questions regarding credibility and reflections on ethical issues related to the project are considered.